Inverse Kinematics Assistance for the Creation of Redirected Walking Paths - Thomas, Jerald; Yong, Seraphina; Rosenberg, Evan Suma (2022 IEEE International Symposium on Mixed and Augmented Reality (ISMAR), 2022)
Virtual reality interactions that require a specific relationship between the virtual and physical coordinate systems, such as passive haptic interactions, are not possible with locomotion techniques using redirected walking. To address this limitation, recent research has introduced environmental alignment, which is the notion of using redirected walking techniques to align the virtual and physical coordinate systems such that these interactions are possible. However, the previous research has only implemented environmental alignment in a reactive manner, and the authors posited that better results could be achieved if a predictive algorithm was instead used. In this work, we introduce a novel way to model the environmental alignment problem as a version of the inverse kinematics problem which can be incorporated into several existing predictive algorithms, as well as a simple proof-of-concept implementation. An exploratory human subject study (N=17) was conducted to evaluate this implementation's usability as a tool for authoring planned path redirected walking scenarios that incorporate physical interactivity. To our knowledge, this is the first study to evaluate redirected walking experience design tools and provides a possible framework for future studies. Our qualitative analysis of the results generated both guidance for integrating automatic solvers and broad recommendations for designing redirected path authoring tools.